The Relationship Between Spiritual Well-Being and Psychological Distress in Indonesian College Students - Devina Terencia Mulholland; Fikrotul Hanifah (Journal of General Education and Humanities, 2026)
This study addresses the high prevalence of psychological distress among university students in Indonesia and the limited empirical evidence regarding protective psychological resources within a religious–cultural context. The objective of this research is to examine the relationship between spiritual well-being and psychological distress, including its core dimensions of depression, anxiety, and stress. A quantitative approach was employed using a cross-sectional correlational design. Data were collected from 327 undergraduate students via an online survey using the Spiritual Well-Being Scale (SWBS) and the Depression, Anxiety, and Stress Scale (DASS-21). The data were analyzed using Spearman’s Rho correlation technique. The findings demonstrate a strong and statistically significant negative relationship between spiritual well-being and overall psychological distress (ρ = −0.662), indicating that higher spiritual well-being is associated with lower levels of psychological distress. Further analysis revealed that spiritual well-being was most strongly related to depression (ρ = −0.715), followed by anxiety (ρ = −0.618) and stress (ρ = −0.476). These results confirm the role of spiritual well-being as a significant protective factor against psychological distress among Indonesian university students.